Pra-Desain Wisata Hijau Sempadan Sungai dan Community Center Kampung Lengkong Kyai, Tangerang - Banten - Muhammar Khamdevi; Andrey Caesar Effendi; Moses Lo; Muhammad Gerry Malik Prahasta; Nur Hakim Rusli; Leon Liauwnardy (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Lengkong Kyai Village is a Historical Heritage Village in Tangerang Regency. The existence of this village is increasingly surrounded and isolated by the development of modern formal housing in BSD City, so that its physical condition is increasingly became slum and its identity as a historical heritage village is decreasing. The Tangerang Regency Government has directed this village as a Pilgrimage Tourism Village, but has not yet had a thorough plan. Therefore, the KKL and PKM activities of the Architecture Study Program tried to plan a design that was focused on the Cisadane River side of this village, because this side is where the village is easily recognizable from the main road of BSD City. This activity resulted in a pre-design of green tourism and a community center on the river border that was connected to historical heritage objects in the village so that it became a unified program of spiritual or religious tourism activities.